Angel of the cove [large type] - Robbins, Sandra (Sandra S.) (Center Point Publishing, 2012)
"It's 1894, and Anna Prentiss has never wanted to be anything but a nurse. But before she can start school in New York City, her brother sends her to Cades Cove, deep in the Smoky Mountains, to spend a summer apprenticing to the local midwife. Anna is determined to prove herself, and then head to the big city. But nothing could have prepared Anna for the beauty of the Cove or the community and friendships she finds there. And she certainly wasn't prepared for Simon Martin, the handsome young minister, or the feelings he arouses in her. Has God's plan for Anna changed? Or is she just starting to hear Him clearly? From the banks of the Mississippi River to the Black Belt of Alabama, to the Smoky Mountains in Tennessee, and the Outer Banks of North Carolina, Sandra Robbins' characters take her readers on a faith-filled journey as they experience life in the South. In Angel of the Cove, she weaves a tale of love, loss, and God's faithfulness" -- Cover verso.